The Football Stadium in Morocco and the Dynamic of Struggle Over the Truth System, the Ultras Against the State - Blaiha, Marouan; Elhoucine, Oughlane (Advances in Social Sciences Research Journal, 2022)
The football stadium has increasingly transformed from being a site of sport and football-supporting teams into a site of expressing social frustration. This transformation has been noticeable in Morocco since 2010, where the stadiums have become a remarkable space to criticize the political performance and policies of certain political institutions. Consequently, several clashes occurred between the ultras and the state, which endlessly looking for strategies to stop the ultras from gaining social ground. On the other hand, the new actors (ultra) seem to create a new aesthetic sense with their depicted non-usual political signs. In this regard, we argue that the limited space for participation (stadiums) defines two conflicting dynamics over the system of truth. In the same vein, the aesthetic practices in the stadiums are combating the dominant systems of truth by generating a "new distribution of the sense" which the ultras strongly believe in. To make this epistemic claim, we based our analysis on the theoretical contributions of the French philosopher Jacques Ranciére, which were deeply discussed and analyzed in his book "The politics of aesthetics: the distribution of the sensible.